2021
DOI: 10.18186/thermal.867134
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Enhancement in Electroosmotic Micromixers

Abstract: Micromixers have important applications in various pharmaceutical and medical fields. In the present study, the enhancement of mixing index in electroosmotic micromixer with different geometries is investigated. The commercial software COMSOL Multiphysics 5.4 is employed to solve the mathematical models. The SIMPLEC algorithm is employed for coupling the velocity and pressure fields. A second-order upwind scheme is used to reduce the artificial diffusivity. The results show a remarkable effect of the electric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…They have employed passive and active techniques. Magnetic field [5,6,8,10], acoustic field [7,18], and electrophoresis [9,11,16,17] are three types of active methods that improve mixing efficiency. It can be found that molecular diffusion is dominant when Re is low and chaotic advection plays a major role when Re is high.…”
Section: Micromixingmentioning
confidence: 99%
“…They have employed passive and active techniques. Magnetic field [5,6,8,10], acoustic field [7,18], and electrophoresis [9,11,16,17] are three types of active methods that improve mixing efficiency. It can be found that molecular diffusion is dominant when Re is low and chaotic advection plays a major role when Re is high.…”
Section: Micromixingmentioning
confidence: 99%
“…To improve the mixing quality, various active and passive techniques have been utilized by many researchers [2]. Passive methods do not employ external energy sources, while active techniques, such as magnetophoresis [3][4], acoustic force [5][6], electroosmosis [7], etc., utilize external actuators.…”
Section: Introductionmentioning
confidence: 99%